The Nucleolar Localization Signal of Porcine Circovirus Type 4 Capsid Protein Is Essential for Interaction With Serine-48 Residue of Nucleolar Phosphoprotein Nucleophosmin-1 - Zhou, Jianwei; Qiu, Yonghui; Zhu, Ning; Zhou, Linyi; Dai, Beining; Feng, Xufei; Hou, Lei; Liu, Jue (Frontiers in Microbiology, 2021)
Porcine circovirus type 4 is an emerging etiological agent first detected in 2019. The nucleolar localization signal of porcine circovirus type 4 capsid protein (PCV4 Cap) and its binding cellular host proteins are still not elucidated. Here, we report a previously unidentified nucleolar localization signal (NoLS) of PCV4 Cap, which interacts with the nucleolar phosphoprotein nucleophosmin-1 (NPM1). The NoLS of PCV4 Cap and serine-48 residue of N-terminal oligomerization domain of NPM1 are essential for PCV4 Cap/NPM1 interaction. In addition, charge property of serine-48 residue of NPM1 is critical for its oligomerization and interaction with PCV4 Cap. Taken together, our findings demonstrate for the first time that the NoLS of PCV4 Cap and oligomerization of NPM1 determines Cap/NPM1 interaction.